MEKANISME EKSTERNAL VS MEKANISME INTERNAL PADA KONSERVATISME AKUNTANSI:MANA YANG LEBIH EFEKTIF? - Viriya Dewi; Deasy Ariyanti Rahayuningsih (Jurnal Bisnis dan Akuntansi, 2023)
The fundamental purpose of this study is to get empirical evidence that influence accounting conservatism on non financial listed company. This study selected seven variables are litigation risk, managerial ownership, institutional ownership, debt covenant, board size, independent commissioners, and leverage as independent variable. The population in this study is non financial companies listed in Indonesia Stock Exchange (IDX) over the three years periode 2018-2020. This study used 633 sample data that selected using purposive sampling method. Hypothesis in this research was analyzed by multiple linear regression. The result of this study indicate that litigation risk, board size and leverage have influence towards accounting conservatism. Beside another independent variables such as magerial ownership, institutional ownership, debt covenant, and independent commissioners have no influence toward accounting conservatism.